The importance of Indigenous cultural burning in forested regions of the Pacific West, USA - Long, Jonathan W.; Lake, Frank K.; Goode, Ron W. (Forest ecology and management, 2021)
[Display omitted] •Tribes want to address contemporary threats to well-being with cultural burning.•Cultural burning supports material and nonmaterial needs and broader services.•Experiments face various challenges in quantifying benefits of cultural burning.•Long-term collaborations based on frequent burning would help to evaluate impacts. Indigenous communities in the Pacific West of North America have long depended on fire to steward their environments, and they are increasingly asserting the importance of cultural burning to achieve goals for ecological and social restoration. We synthesized literature regarding objectives and effects of cultural burning in this region within an ecosystem services framework. Much scholarly literature focuses on why various species harvested from burned areas were important historically, while tribes and recent research increasingly stress a wide range of ecological and cultural benefits afforded by contemporary cultural burning. These tribal values generally align with broader ecological restoration objectives, although Indigenous practitioners espouse holistic views on the benefits of burning rather than focusing narrowly on fuel reduction and wildfire mitigation. While government agencies are motivated to treat more and larger areas to reduce fire risk (expanding pace and scale), tribal practitioners have tended to burn comparatively small areas at one time, and cumulatively due to various constraints. However, they would like to burn more widely and frequently to promote resilience to wildfire and drought; conserve biocultural diversity, maintain traditional knowledge and spiritual values; and provide material goods such as foods, medicines, and fiber materials. Much of the experimental research on the effects of cultural burning has been conducted as graduate research and has tended to look at single burns (sometimes agency prescribed burns or wildfires rather than tribally-led cultural burns) for short periods in very limited contexts. Such studies have found that treatments often promote desirable plant qualities, including reduced incidence of pests and structural qualities that facilitate weaving and other crafts. However, effects on understory plant diversity, wildlife, fruit production, parasites, and other key aspects of resource quality have been more difficult to evaluate due to complex interactions and scale considerations. Expanding long-term tribal collaboratives, including designating cultural management areas with frequent burning, would help to understand the potential to achieve ecocultural restoration objectives.